Pengkajian Makna Gibah dalam Perspektif Hadis: Studi Takhrij dan Syarah Hadis - Fadia Luthfi Riyani (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about grumbling. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about grumbling in Abu Daud's narration No. 4231. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi which is maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narrated by Abu Daud No. 4231 is relevant to be used as a way to avoid gossip or gibah.